Kandungan flavanoid total dan aktivitas antimikroba serbuk biji kakao (Theobroma cacao) asal kabupaten enrekang Sulawesi Selatan - Emelda, Andi; Rusli, Rusli; Nurlina, Nurlina; Santi, Irma (Universitas Ahmad Dahlan, 2016)
Cocoa and its derivatives are rich in flavonoids. Flavonoid content of cocoa beans is affected by the treatment process. The aim of this study are to determine total flavonoids and antimicrobial activity of cocoa powder. This study used unfermented cocoa beans in the form of powder. Testing of the total flavonoids was conducted using an aluminum chloride colorimetric assay. The minimum inhibitory concentration (MIC), Minimum Bactericidal Concentration (MBC), and antimicrobial activity of cocoa bean powder were tested by using ten bacteria: Staphylococcus epidermidis, Bacillus subtilis, Escherichia coli, Salmonella thypi, Shigella dysentriae, Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus mutans, Vibrio cholerae, and Propioni bacterium agne. The result of measurement of the total flavonoid of unfermented cocoa powder is 22.62 mg EC/g. The screening of antimicrobial with concentration of 0.1% of cocoa powder gives inhibition in Streptococcus mutans, dysentriae Shigella, Escherichia coli, Vibrio cholerae bacterium and Propioni bacterium agne, while at a concentration of 0.5% gives inhibition at all test bacteria. In the antimicrobial activity test using a concentration of 0.5%, 1%, 2% and 4%, the highest resistance zone is shown at a concentration of 4 %. The results show that the diameter zone of inhibition for the bacteria Shigella dysentriae is 11.33 mm. The 10 mm of diameter zone of inhibition are indicated by streptococcus mutans, Escherichia coli, Propioni bacterium agne, Staphylococcus aureus and Bacillus subtilis while 11 mm zone of inhibition demonstrated by Salmonella thypi and Staphylococcus epidermidis. The number of the diameter zone of inhibition, 12 mm, was shown in Pseudomonas aeruginosa. In conclusion, the powder of unfermented cocoa beans provides flavonoids 22,62 mg EK/g and have the antimicrobial activity.